1999
DOI: 10.1108/08876049910298739
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a video screen and rotational‐signage systems on satisfaction and advertising recognition

Abstract: Examines the impact of a video screen on spectator satisfaction and the advertising effectiveness of rotational-signage systems. A total of 181 spectators at a major college football game were interviewed during the half-time of a regular season contest. Results demonstrate that the screen is a significant component of a stadium's servicescape which can increase the satisfaction of fans and their intentions to attend future events. While fans recognized less than half the companies that were advertised, firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…Only the two main sponsors of the event use larger boards and also take positions that typically guarantee longer viewer exposure times, such as behind the players, in the corner or close to the time-keeping devices and scoreboards. Industry experts consider recall scores above 10% high (Wright 1988), and the recognition rates of sponsors with reduced visibility often fall below the 20% levelsometimes even approaching 0% (Moore et al 1999). Therefore, we do not expect the conscious memory effect to be strong; however, spectators may remember the sponsor brand better than the control group does, in terms of both recall and recognition.…”
Section: Research Hypothesesmentioning
confidence: 81%
“…Only the two main sponsors of the event use larger boards and also take positions that typically guarantee longer viewer exposure times, such as behind the players, in the corner or close to the time-keeping devices and scoreboards. Industry experts consider recall scores above 10% high (Wright 1988), and the recognition rates of sponsors with reduced visibility often fall below the 20% levelsometimes even approaching 0% (Moore et al 1999). Therefore, we do not expect the conscious memory effect to be strong; however, spectators may remember the sponsor brand better than the control group does, in terms of both recall and recognition.…”
Section: Research Hypothesesmentioning
confidence: 81%
“…These studies have generally concluded that sponsorship of sports events can be effective. In several studies, it has been found that the majority of spectators can recall at least one sponsor correctly (Biscaia et al , 2014; Lee and Bang, 2005; Moore et al , 1999; Stotlar and Johnson, 1989; Turley and Shannon, 2000). Other studies used the mean number of sponsors recalled to evaluate the effectiveness of sponsorship.…”
Section: Executive Summarymentioning
confidence: 99%
“…Television sponsorship, perhaps due to its similarity to spot advertising, is one of the formats for which the effects on audience recall have been analysed. Most papers establish a positive correlation between its use and cognitive effects on the audience (Lardinoit, 1998;McDaniel, 1999;Moore et al, 1999).…”
Section: Effectiveness On a Cognitive Levelmentioning
confidence: 99%